Reliability and validity of an instrument to describe burnout among collegiate athletic trainers - Clapper, D. C.; Harris, L. L. (Journal of Athletic Training, 2008)
The existing investigations of professional burnout among certified athletic trainers (ATs) were conducted before 2000. Since 2000, several educational and legal changes have redefined the job duties and responsibilities of the AT working in collegiate athletics.